2015
DOI: 10.1007/s00127-015-1040-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional time trends in psychological and somatic health complaints among adolescents: a structural equation modelling analysis of ‘Health Behaviour in School-aged Children’ data from Switzerland

Abstract: 2 ABSTRACTPurpose: This study examined cross-sectional time trends in health complaints among adolescents living in Switzerland, including differences between population subgroups and sources of differential response to items.Methods: Swiss data were analysed from the Health Behavior in School-aged Children (HBSC; including 11-to 15-years old) from 1994 (n=7008), 1998 (n=8296), 2002 (n=9066) and 2006 (n=9255). Structural equation modelling was used to assess 1) the structure of the HBSC Symptom Checklist (HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 30 publications
8
46
2
2
Order By: Relevance
“…Schoolchildren who used computer and watched TV for ≥240 min showed higher rates of LBP (46%) compared with those who watched TV and used computer for ≤240 min. The data of our study were in accordance with previous cross-sectional studies that reported a significant association between LBP and time spent watching television92 and playing video games;93 however, this association was not found in other studies 94…”
Section: Discussionsupporting
confidence: 92%
“…Schoolchildren who used computer and watched TV for ≥240 min showed higher rates of LBP (46%) compared with those who watched TV and used computer for ≤240 min. The data of our study were in accordance with previous cross-sectional studies that reported a significant association between LBP and time spent watching television92 and playing video games;93 however, this association was not found in other studies 94…”
Section: Discussionsupporting
confidence: 92%
“…The two factors correlated .80. This estimate is not very different from the correlation of .73 found by Dey et al () between the HBSC Psychological and Somatic factors. The relatively high interrelation between the mental health factors may be because of the fact that some depressive or affective symptoms lead to somatic symptoms such as muscle tension, difficulties to sleep or poor appetite.…”
Section: Methodscontrasting
confidence: 49%
“…Analyses of the dimensionality of the eight items have shown that a one‐dimensional model does not fit the data, while a model with two correlated dimensions does (e.g. Dey, Jorm, & Mackinnon, ). Thus, emotional distress and psychosomatic problems are two partly overlapping aspects of internalizing mental health problems, which both need to be covered.…”
Section: Methodsmentioning
confidence: 99%
“…Common ways are to look at (a) self-reported mental health from youth themselves, (b) statistics for youth diagnosed with a psychiatric condition, or (c) statistics for youth on medication for psychiatric conditions. For investigating mental health problems among youth via self-reports, researchers are advised to also include somatic health complaints (e.g., headache, backache, stomachache, and dizziness), since the combination of mental and somatic complaints often are considered to be a unidimensional factor (Dey et al, 2015). A Swedish study shows that self-reported mental and somatic complaints doubled among Swedish 15-year-olds from 1985 to 2014 (Folkhälsomyndigheten, 2014).…”
Section: Why Do Young Girls Report More Mental Health Problems Comparmentioning
confidence: 99%